1999
DOI: 10.1093/tropej/45.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Ankle clonus and thiocyanate, linamarin, and inorganic sulphate excretion in school children in communities with konzo, Mozambique

Abstract: We examined 397 school children for ankle clonus in five communities in three districts affected by konzo, spastic paraparesis associated with cassava consumption. From a subsample of 131 children, we analysed urine specimens for urinary thiocyanate, linamarin, and inorganic sulphate. The proportion of children with clonus varied between sites, ranging from 4 to 22 per cent. Geometric mean thiocyanate, linamarin, and inorganic sulphate concentrations were 163 and 60 mumol/l and 4.4 mmol/l, respectively. Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Cliff and colleagues [58] also reported on a project where they examined 397 children for ankle clonus in three districts previously affected by konzo. The study found that the proportion of children with clonus ranged from 4% to 22%.…”
Section: Resultsmentioning
confidence: 99%
“…Cliff and colleagues [58] also reported on a project where they examined 397 children for ankle clonus in three districts previously affected by konzo. The study found that the proportion of children with clonus ranged from 4% to 22%.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of cyanide toxicity from cassava is increased because not only is the part that is consumed highly cyanogenic but it also frequently forms a large proportion of the overall diet. Sulphur-containing amino acids (methionine and cysteine) are required to detoxify cyanide in humans [70,99,100] (see Figure 6). Cassava tubers are a poor source of protein, and the leaves, which are eaten as a protein supplement, are particularly low in these amino acids [101].…”
Section: Cyanogens In Cassava: Impacts On Human Healthmentioning
confidence: 99%
“…Second, key biomarkers e.g. those of exposure to cyanogenic compounds such as the urinary levels of thiocyanate (SCN) do display poor fidelity to the individual diseases listed above (Lancet, 1984, Banea-Mayambu et al, 1997, Cliff et al, 1999). Third, there appear to be a wide spectrum of neuropathological features in the same individual diseases (Oluwole et al, 2000, Tshala-Katumbay et al, 2001b, Tshala-Katumbay et al, 2002a, Tshala-Katumbay et al, 2002b, Mwanza et al, 2003b, Madhusudanan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%